The Role of Good Corporate Governance (GCG) in Improving Workforce Performance and Corporate Culture: Peranan Good Coorporate Governance (GCG) Dalam Meningkatkan Kinerja Tenaga Kerja Dan Budaya Perusahaan - Mudjib, Affandy Winarko; Setiyono, Wisnu Panggah (Indonesian Journal of Law and Economics Review, 2022)
In service companies, the performance of human resources is one of the benchmarks for calculating company productivity. Anticipating that a crisis like 1997 would not return, the Indonesian government requires companies under the status of the Ministry of State-Owned Enterprises (BUMN) to implement GCG. Character building of the workforce is the duty of the company in shaping the work pattern of the company's workforce, one of which is the goal of establishing the Good Corporate Governance (GCG) program. These things are currently the responsibility of PT Pegadaian (Persero). For this reason, this study aims to determine the effect of the Good Corporate Governance (GCG) system that has been set on the performance of the workforce and the condition of Corporate Culture at PT Pegadaian Surabaya Regional Office. And know the reputation of PT Pegadaian (Persero) in the eyes of the public since the implementation of the Good Corporate Covernance (GCG) system? Based on several theories and previous research that discusses Good Corporate Covernance (GCG); Labor Performance; Corporate Culture; Company Reputation. The method used is a qualitative method by processing data using Actor Network Theory. In conclusion, the Good Corporate Covernance (GCG) system that has been implemented has an influence on the performance of the workforce and the condition of the Corporate Culture at PT Pegadaian Surabaya Regional Office. Meanwhile, the reputation of PT Pegadaian (Persero) in the eyes of the public since the implementation of the Good Corporate Covernance (GCG) system has increased.